NEW RESULTS FOR THE P-12C RADIATIVE CAPTURE AT LOW ENERGIES - D. M. Zazulin; N.Burtebayev; R. J. Peterson; S. V. Artemov; S. Igamov; Zh.K. Kerimkulov; D. K. Alimov; E. S. Mukhamejanov; Maulen Nassurlla; A. Sabidolda; Marzhan Nassurlla; R. Khojayev (Academic Scientific Journal of Computer Science, 2019)
New measurements of the differential cross sections of the 12C(p,γ)13N radiative capture reaction at the angle 00 for the transition to the ground state in 13N have been made at the energies of incident protons from 1088 to 1390 keV (uncertainties of about 12%). Based on the obtained differential cross sections and on the assumption that the angular distributions are isotropic in this energy region, the 12С(p,γ)13N reaction astrophysical S-factors have been determined for the transition to the ground state in 13N with an uncertainties of about 16%. Within the limits of uncertainties, our experimental results are consistent with the previous data. Analysis of the 12C(p,γ)13N reaction astrophysical S-factor at low energies has been carried out within the modified R-matrix approach by using previously measured asymptotic normalization coefficient of the overlap integral of the wave functions of 12C and 13N nuclei bound states to minimize the uncertainties due to calculation of the direct capture part of the 12C(p,γ)13N reaction astrophysical S-factor at extremely low energies. For the energies of 0.25 and 50 keV in center of mass frame the calculated values of the 12C(p,γ)13N reaction S-factors for the transition to the ground state in 13N are presented. In the temperature range from 0 to 1010 K the rates of the 12С(p,γ)13N fusion reaction have been obtained. The results of our calculations are compared with the experimental and calculated results of previous works.